Optimizing Heritage Power Distribution Using Zonal TM/TR-Package Systems - Suparjo Suparjo; R. Kun Wardana Abyoto; Hendro Tjahjono (International Journal of Engineering Continuity, 2026)
Electrical power distribution in heritage conservation areas faces the dual challenge of meeting modern technical standards while adhering to strict preservation regulations. Traditional centralized low-voltage systems often result in critical voltage drops and power losses due to extended feeder lengths. This study proposes and evaluates an optimized Zonal TM/TR-Package distribution system as a solution. Using ETAP 22.5 software, a comparative load flow analysis was conducted on a 20-hectare government heritage complex comprising 21 protected buildings. The simulation results confirm that the proposed zonal configuration significantly outperforms the existing centralized system, reducing maximum voltage drops from 12.04% to 4.48% and decreasing total active power losses (I2R) by 47.6%, and improving system efficiency from 95.32% to 97.50%, ensuring full compliance with PUIL 2020 safety standards. Critically, the reliability assessment — evaluated using SAIDI and SAIFI indices — demonstrates a 37.44% improvement in SAIDI (from 9.27 to 5.80 hours/customer/year), while SAIFI remains stable at 0.77 interruptions/customer/year, confirming that zonal fault isolation substantially reduces outage duration without increasing interruption frequency. Furthermore, the modular design minimizes physical footprint, preserving the site’s aesthetic value. Beyond a case study, this research contributes to electrical engineering science by establishing a replicable technical framework for revitalizing heritage infrastructure, balancing efficient power delivery with architectural conservation.